The Role of “Penggerak” and Independent Principal as Manager - Widodo; Sudarwan Danim; Asti Putri Kartiwi (Universitas Bengkulu, 2023)
This study aims to determine the role of the principal regarding programming, organizing, activating and supervising at SMPN 21 Seluma and at SMPN 24 Kota Bengkulu. The research method used is descriptive qualitative, with research subjects being principals, teachers, administrative staff engineering data collection using interviews, observations, and documentation. Data analysis techniques by collecting data, analyzing data, presenting data, and drawing conclusions, and testing the validity of the data are carried out with credibility which includes triangulation, transferability, dependability and confirmability. Research shows that school principals plan detailed HR, policies, curriculum by involving teachers, committees. Organizing begins with compiling the school's organizational structure, division of competence. Mobilizing teachers and staff by providing directions and guidance, motivating employees to take part in training seminars, workshops, continuing studies and holding monthly evaluation meetings, supervision bymeans of; observing attendance discipline, learning process, seeking information through the school's deputy head and colleagues, and conducting supervision.